Analisis Pengaruh Transaksi Hubungan Istimewa dan Struktur Modal Terhadap Penghindaran Pajak Dengan Kepemilikan Asing Sebagai Variabel Moderasi - Aziz Kardinto, Fuad; Muktiyanto, Ali; Christya Rahayu, Heffi (Journal of Accounting and Finance Management, 2025)
The main source of state funding is taxation. Nonetheless, tax evasion remains widespread in Indonesia. In order to demonstrate that foreign ownership can somewhat mitigate the impact of related party transactions, capital structure, profitability, and asset growth on tax avoidance, this study will test and assess the relationship between these factors and tax avoidance. The industrial sector companies listed on the Indonesia Stock Exchange between 2015 and 2021 were the subjects of this quantitative study. Purposive sampling was employed, consisted of 18 businesses. Multiple regression analysis and the Moderated Regression Analysis test with absolute value difference approach were used. The results indicate that capital structure has an impact on tax evasion but related-parties transactions have no influence. The relationship between capital structure and tax avoidance, asset growth and tax avoidance, and related-parties transactions and tax avoidance can all be moderated by foreign ownership, however profitability and tax avoidance cannot be moderated.